Correlation of Angiotensin-converting Enzyme 2 Gene (rs1514283) Polymorphism with the Incidence of COVID-19 - Hams Hussain Hashim Al-Fattli; Tabarek Salam Abd-Alraoof (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
It has been a busy year for coronaviruses, with the most recent one causing severe coronavirus illness in 2019 (COVID-19). It is broadly distributed in many human tissues and organs as the potential SARS-CoV-2 receptor angiotensin-converting enzyme 2 (ACE2). ACE2 provides homeostatic modulation of circulation angiotensin II levels by acting as a physiological counterbalance to ACE. They have been linked to COVID-19 disease acquisition, progression, and severity. As a result, we investigated how ACE2 variations and epigenetic variables affect SARS-CoV-2 infection susceptibility and infection outcomes in terms of age, gender and ethnicity. Debates raged over an etiology of this occurrence. It is important to note that further research is required to demonstrate the efficacy of human recombinant ACE2 and ACE2-derived peptides in fighting SARSCoV-2 variants. A better recognition of a host genetic as well as the function of the proerties of ACE2 variations would assist in explaining clinical disparities of infection between individuals and contributing in development of remedies and managing future SARS-CoV-2 epidemics, an essential function for ACE2 in Essential Hypertension (EH). We wanted to see how ACE2 gene polymorphisms and enzyme activity correlated with COVID-19 incidence in the Iraqi province of Al-Diwaniya! 63 COVID-19 patients and 70 (NT)controls were genotyped using Sequenom Mass-ARRAY RS1000 for ACE2. Participants' ACE2 rs1514283 SNP was linked to COVID-19.